Semantics interfaces - Maienborn, Claudia; Heusinger, Klaus von; Portner, Paul (Mouton reader., 2019)
"Explore the exciting research where semantics meets morphology, syntax and pragmatics. In this book, leading researchers use in-depth articles to explain a wide range of topics at these interfaces, including the semantics of intonation, inflection, compounding, argument structure, type shifting, compositionality, implicature, context dependence, deixis and presupposition. Now in paperback for the first time since its original publication, the highly cited material in this book is an ideal starting point for anyone interested in semantics where it crosses over with other dimensions of grammar"--